The reality of Organizational justice practices in the academic environment and its impact on the behavior of bullyingField study on faculty members in King Abdulaziz University in Jeddah - Al Rasheed, Malak Mohammad; Alshamasi, Areej Abdulrhman (Journal of Economic, Administrative and Legal Sciences, 2019)
The study aimed at identifying the organizational justice degree together with its distributive, procedural, interactive and evaluation dimensions in the academic environment. As well as to identify the bullying degree between the faculty members in the academic environment. Detecting any of the regulatory justice dimensions has more contributive degree in mitigating the bullying conduct.The descriptive approach (analytical) has been used to achieve the aims of this study, the researcher distributed a questionnaire (a soft and a hard copy) which contains 38 statement as a tool to collect data. The study society is composed of 2918 faculty members. A random proportional sample of 340 members and 240 male faculty members and 100 female faculty members. Data has been statistically processed using the statistical packages of social sciences. This study achieve many results, the most important thereof is the practicing degree of organizational justice in University of King Abdulaziz, from the point of view of the faculty members was medium degree at 69.4 %. The degree of bullying in the University of King Abdul Aziz, from the point of view at medium degree is 46.8 %. Exercising the organizational justice with its distributive, procedural, interactive and dealings dimensions in affecting the bullying conduct, the distributive justice occupies the largest influence on the bullying conduct, with bullying effect 6.27 %. After that the procedural justice with influence 03.58 %. Then the interactive and dealing justice with influence 2.84 %. In light of these results, the study achieved many recommendations, the most important thereof is the establishment of training courses to keep the academic vice deans and new Heads of Departments in the college, and confirm training them before and after having administrative positions aware of the importance of applying and practicing the organizational justice in the university and its role to mitigate harmful conducts, including bullying. As well as establishment of training courses to keep all faculty member of both genders, of any academic degrees, about the nature of bullying conduct in the work environment, with its forms and damages, as well as the methods of dealing with this conduct.
Keywords: organizational justice; distributive justice; procedural justice; interactive justice; evaluative justice; bullying behaviour